1972
DOI: 10.1111/j.1399-0004.1972.tb01482.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis in the 46, XX, 18p‐ syndrome

Abstract: Some of the evidence suggesting a relationship between autoimmunity and chromosomal aberrations is reviewed and an example which may support such a relationship is presented. The propositus was a 5‐year‐old Caucasian female who had juvenile rheumatoid arthritis and a deletion of the short arm of a chromosome 18 (46, XX, 18p‐). Her serum IKA was normal, although IgA deficiency has been reported in a significant number of patients having an 18 deletion syndrome as well as in patients having rheumatoid arthritis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The unique feature of our patient was her late onset of RA compared to the early JRA previously reported 5 – 9 , 10 . Our patient was RF positive, anti-CCP negative and met 9/10 of the 2010 American College of Rhematology (ACR) Clinical Classification Criteria for RA 7 . To the best of our knowledge there have been seven reported, and six published, cases of RA associated with chromosome 18 abnormalities ( Table 1 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The unique feature of our patient was her late onset of RA compared to the early JRA previously reported 5 – 9 , 10 . Our patient was RF positive, anti-CCP negative and met 9/10 of the 2010 American College of Rhematology (ACR) Clinical Classification Criteria for RA 7 . To the best of our knowledge there have been seven reported, and six published, cases of RA associated with chromosome 18 abnormalities ( Table 1 ).…”
Section: Discussionmentioning
confidence: 70%
“…Daentl first mentioned an unpublished case of JRA in a patient with 18p- and IgA deficiency 8 . In the first published case, Finley et al reported a 9-month-old female with 18p-, swelling and contractures in many joints, fever, rash, and hepatosplenomegaly, consistent with JRA 7 . JRA has subsequently been associated with cases of 18q- as well 6 , 8 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there has also been a suggestion of a link between PTPN2 and rheumatoid arthritis and type 1 diabetes [Todd et al, ; Okada et al, ]. Rheumatoid arthritis has been reported in individuals with 18p‐ [Finley et al, ; Czakó et al, ; Recalcati et al, ]. Thus, it seems plausible that PTPN2 plays a role in etiology of autoimmune disease.…”
Section: Gene Dosage Mapmentioning
confidence: 99%
“…As the number of case reports increased, additional findings were described, to include speech and language difficulties, pituitary abnormalities, and, in some cases, IgA deficiency [Schinzel et al, ; Artman et al, ; Gul et al, ; Schober et al, ; McGoey et al, ]. More recently, the phenotype has expanded to include dystonia and autoimmune conditions, such as rheumatoid arthritis [Finley et al, ; Gluckman, ; Jones, 1982; Brown et al, ; Graziadio et al, ; Postma et al, ; Recalcati et al, ; Kowarik et al, ]. As is the case with many chromosomal abnormalities, however, the earliest reports had little information about breakpoints or genotype–phenotype correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient was RF positive, anti-CCP negative and met 9/10 of the 2010 American College of Rhematology (ACR) Clinical Classification Criteria for RA 7 . To the best of our knowledge there have been seven reported, and six published, cases of RA associated with chromosome 18 abnormalities ( Table 1).…”
Section: Discussionmentioning
confidence: 70%